Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam dengan Model Discovery Learning Materi Energi dan Perubahannya pada Siswa Kelas VI SDN 1 Sukamenanti, Bandar Lampung - Kusrina Kusrina (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The objectives of this study are to knowing the improvement of learning outcomes in the Natural Science Matari Energy and its changes after the application of the Discovery Learning model in Class VI semester II students of SDN 1 Sukamenanti, Kedaton District, Bandar Lampung City, 2017-2018 Academic Year. This research uses action research as many as three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the sixth grade students of SDN 01 Sukamenanti, Kedaton District, Bandar Lampung City, 2016-2017 Academic Year. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (26.31%), cycle II (47.36%), cycle III (89.47%).